Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Endothelial-Mesenchymal transition in cerebrovascular diseases: molecular mechanisms and promising pharmacological strategies - Jinlin Xiao; Canyang Yu; Dianda Chen; Feng Lin; Shuhua Zhang; Daya Luo; Erming Zeng (Molecular Biology Reports, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Selective recovery of palladium from actual acidic wastewater using a covalent triazine framework: The critical enabling role of chloride ions - Junyi Yu; Qingying Xiao; Ziwen Chang; Jianzhi Zhang; Hao Dong; Jiaochan Zhong; Lin Ding; Yidi Chen; Xubiao Luo; Penghui Shao (Water Research, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Biostratigraphic and paleobiogeographic significance of two cap-shaped fossil groups from the Cambrian Xinji Formation, North China: Evidence for North China–Australia faunal links - Meng Gong; Hong Hua; Yang Hou; Xinzi Wang; Song Zhang; Zihui Wu; Xueting Wang; Ling Yu; Yan Tan; Jinzhou Luo; Lin Bai (Journal of Asian Earth Sciences, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Enzymatic synthesis and structural characterization of Sn-2 α-linolenic acid-enriched structured lipids from cottonseed oil via 13C NMR and UPLC-MS/MS - Shiyang Yu; Shiyu Yu; Hexi Yuan; Yanhong Lin; Changqing Wei; Peng Luo (Food Research International, 2026)

Endocrine-disrupting chemical-induced gene networks confer coronary heart disease risk revealed by causal inference and single-cell analyses - Tao Yao; Yun-Lu Lin; Luo-Xiang Fang; Yu-Tian Wang; Lan-Feng Zhou; Ning Zhang; Gang Chen (Food and Chemical Toxicology, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Synergistic effects of biochar and probiotic fermentation agent on soil aggregate stability, carbon sequestration, and heavy metal(loid)s passivation in paddy fields - Keqi Zhao; Xue Yu; Xifeng Qin; Ruijie Li; Lin Luo; Xiaomei Yang; Liuqin He; Anwei Chen; Jiachao Zhang; Hongli Huang; Xichen Zhao (Agriculture, Ecosystems & Environment, 2026)

A new biostratigraphic marker for Cambrian Stage 3 on the Northern Margin of the Yangtze Platform: Mianxiantubus–Pelagiella subangulata assemblage subzone - Xueting Wang; Hong Hua; Jinzhou Luo; Yang Hou; Meng Gong; Song Zhang; Xinzi Wang; Zihui Wu; Yan Tan; Ling Yu; Lin Bai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Nano-island Cu–Cu2O heterojunctions: Synergistic electroreduction of bromate at mixed-valence perimeters - Yu Chu; Junjie Li; Huihuan Lin; Binyu Ma; Zhipeng Luo; Yue Cheng; Xin Yu; Huabin Zeng (Journal of Water Process Engineering, 2026)

Adaptive mechanisms and metabolic evolution of photogranules based on anammox under light irradiation - Zhimin He; Gongduan Fan; Jing Luo; Yu Zhang; Kaiqin Xu; Weiheng Lin (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages” [Food Res. Int. 217 (2025) 116764] - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2026)

Structural characterization of novel polysaccharides from Sargassum fusiforme with dual anticoagulant activity targeting thrombin and antithrombin III - Yue Zhu; Yuanlin Luo; Yunqin Shi; Jiahui Shao; Shunhao Lin; Xiuting Zhang; Yu Tang; Xiangwei Zhao; Jianping Jiang; Zhenzhong Yang (Food Chemistry, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Corrigendum to “Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration” [Carbohydrate Polymers 352 (2025) 123192] - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2026)

Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Water-MAS: A multi-agent LLM framework with instruction-data decoupling for smart water management - Fangkun Lin; Zhipeng Luo; Binyu Ma; Zhiyu Zhang; Kaiyan Liu; Xin Yu; Boyan Xu; Huabin Zeng (Water Research, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Genomic mining of the terpene synthase family in magnoliids reveals novel clades - Fang Wang; Qiongqiong Lin; Zijian Zhang; Yunyang Yu; Mengxue Feng; Meixiu Lin; Yongjuan Ren; Liuming Luo; Xin Liu; Huan Liu; Sunil Kumar Sahu; Tong Wei; et al. (The Nucleus, 2026)

Water-mass structuring of metazoan communities inferred from environmental DNA in the Chukchi Borderland during the summer sea-ice retreat period - Zhiyi Su; Wei Luo; Yong Yu; Kun Liu; Zihan Wang; Zheying Lin; Ling Cao; Cong Zeng (Polar Biology, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

Immune dysregulation and cellular dysfunction mediate di-n-pentyl phthalate–induced hepatotoxicity: Insights from single-cell RNA sequencing - Yu Gan; Yongyi Luo; Xiandong Ye; Kaiyan Zhang; Zhenqiu Xia; Lei Yang; Chaoming Zhou; Gan Xie; Wenyan Zhong; Tengfei Yuan; Shuimiao Lin; Yuan Fang; et al. (Food and Chemical Toxicology, 2026)

Longitudinal trends in serum triclocarban levels from 2008 to 2018: Evidence from the prospective Dongfeng–Tongji cohort study - Caizheng Yu; Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Meian He (Environmental Research, 2026)

Operational stabilization of high-rate partial denitrification-anammox using intermittent low-speed stirring in an expanded granular sludge bed reactor - Zibin Luo; Lan Lin; Weizhe Xia; Yu-You Li (Chemical Engineering Journal, 2026)

Construction of conductive polyimide dressings for accelerated wound healing via an interfacial compatibility optimization and polyelectrolyte complexation synergistic strategy - Lizhi Lin; Kexiang Fan; Hang Luo; Jueying Yang; Huaping Liang; Yongqiang Feng; Lijie Li; Kelin Peng; Yu Chen (Chemical Engineering Journal, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

High-pressure disruption for efficient protein extraction from Chlorella pyrenoidosa: comparative insights with conventional methods - Chen Zhang; Mengqi Nong; Yu Luo; Marco Marcucci; Yihuan Li; Zexin Lin (Innovative Food Science & Emerging Technologies, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Embankment protection-inspired interfacial engineering for ultrahigh-efficiency, stable tandem quantum dot light-emitting devices - Kuibao Yu; Zhihan Lin; Tian Liu; Haolin Luo; Chao Zhong; Hao Liu; Fushan Li; Hailong Hu (Chemical Engineering Journal, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Numerical study of gas-layer drag reduction for a container ship under varied ventilation rate and ship speed conditions - Xiang Lin; Yu Wang; Bo Zhou; Hui Liu; Gaofei Su; Wenqing Luo (Ocean Engineering, 2026)

Mechanistic insights into efficient phenol degradation mediated by anodic respiration in Acinetobacter sp. LA-1 - Binxin Liu; Jingyi Yu; Rongsheng Lin; Wendong Xian; Dan Luo; Li Chen; Jianxin Wang; Wenhui Wang; Qingqing Zhang; Peng Li (Journal of Hazardous Materials, 2026)

Unveiling the superior Pb(II) affinity of sulfonic acid in functionalized UiO-66: A per-functional-group quantification strategy - Shuiping Yu; Yu Luo; Zhiwei Jin; Wenbao Li; Xianglin Zhong; Honggang Zhang; Xinggang Liu; Lin Ding; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

Integrated transcriptomic and functional analyses provide insights into the heat stress response mechanisms and HrcA mediated potential regulatory in Tetragenococcus halophilus JY1 - Fangming Lan; Yu Zhang; Chi Zhao; Jiayi Lin; Dongdong Sun; Juliang Dai; Lixin Luo (Food Bioscience, 2026)

Adapting nitrogen fertilization to increase cotton productivity sustainably and decrease nitrogen loss to the environment - Yu Tian; Feng Shi; Xianzhe Hao; Xiaojuan Shi; Junhong Li; Humei Zhang; Nannan Li; Zemin Li; Hairong Lin; Jiongchao Zhao; Honghai Luo; Karine Chenu (Field Crops Research, 2026)

Formation and evolution of sandy deserts in China: A review - Xin Wang; Ziying Yu; Han Hu; Chongwen Luo; Wenjing Yang; Jiayi Lin; Yu Cao; Zaijun Li; Fei Wang; Baofeng Li; Shengqian Chen; Huayu Lu; et al. (Earth-Science Reviews, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Loss-of-function mutations in PLD4: a new genomics-guided roadmap for type I interferon-centric lupus - Yu-Lin Yao; Li Huang; Yanfei Guo; Baojun Zhang; Rongcan Luo (Science China Life Sciences, 2026)

Distribution characteristics and retention mechanisms of 236U in sediments of the Beibu Gulf - Zhiyi Tu; Xiaolei Zhao; Lin Liu; Xianghao Luo; Yukun Li; Guodong Yu; Manqing Liu; Kaixing Guo; Chunping Huang; Jianhui Lai; Deyu Wang; Huijuan Wang; et al. (Marine Pollution Bulletin, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Electrochemically assisted surface oxidation/activation for ultrathin layered Hv-NiCoCu-OOH @NiCoCu-LDH and research on enhanced energy storage characteristics - Chunxiao Shi; Lin Sun; Fangrong Yan; Yunchao Wu; Weijing Liu; Yu Liu; Qingjun Yang; Guiquan Liu; Runmei Luo; Weidong Shi (Chemical Engineering Journal, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Novel hapten design and highly sensitive monoclonal antibody–based immunochromatographic assay for benzo[a]pyrene in edible oil - Huan-Yuan Xu; Ri-Sheng Chen; Yu Wang; Yue-ming Chen; Sumed Yadoung; Surat Hongsibsong; Peiqiang Shuai; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Exposure trends of neonicotinoids from 2008 to 2018 and health risk in a longitudinal study in China - Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Caizheng Yu; Meian He (Environmental Research, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Solid phase iron-driven Feammox for continuous flow low carbon to nitrogen ratio wastewater: The dual role of functional bacteria recruitment and community coordination optimization - Chisheng Yu; Qiang Lin; Liang Zhu; Ancheng Luo; Xinyu Chen; Kaiying Chen; Tianyu Xu; Zhiwei Liang (Journal of Environmental Chemical Engineering, 2026)

Pivotal effect of oxygen vacancies on S-scheme BiVO4/g-C3N4: Novel dual activation mechanistic studies in photocatalytic selective ethylbenzene oxidation under LED irradiation - Wen-Yu Luo; Ze-Lin Wang; Peng-Jiang Chao; Ying-Ying Xu; Yanfei Xu; Zhuo Li; Lin-Yu Jiao; Mingyue Ding (Chemical Engineering Journal, 2026)

Scale-up analysis of packed-bed ammonia decomposition reactor for efficient hydrogen production using multiscale model - Lixuan Zhang; Minghao Zhang; Li Lin; Wenshi Huang; Chongqi Chen; Dabiao Wang; Huihuang Fang; Yu Luo; Lilong Jiang (Chemical Engineering Journal, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Integrated single-cell multi-omics profiling reveals a senescence-associated hematopoietic landscape and regulatory network in aging bone marrow - Guoyang Zhang; Weixuan Lin; Linghuan Guo; Ziyun Li; Yu Xiang; Luo Wang; Xiaoyu Yan (Biogerontology, 2026)

Stronger Sensitivity of Plant Photosynthesis to Rising CO 2 in High Elevation Ecosystems - Yao Chen; Yangjian Zhang; Zhihua Liu; Shilong Piao; Jingfeng Xiao; Ashley Ballantyne; Philippe Ciais; Josep Peñuelas; Jie Gao; Yongwen Liu; Lin Jiang; Juntao Zhu; et al. (Ecology Letters, 2026)
The CO 2 ‐fertilisation effect (CFE) on vegetation productivity is the major driver of the enhanced land carbon sink in recent decades. CFE theoretically increases with elevation due to the higher sensitivity of carboxylation to an increase of CO 2 under lower CO 2 partial pressure, but the elevation‐dependent CFE pattern has been largely overlooked. By conducting a 6‐year CO 2 enrichment experiment (+100 ppm) in an alpine grassland, we show that elevated CO 2 increased gross primary production (GPP) by 25.5% ± 4.6%. Water availability and plant biomass allocation modulates CFE during different seasons. A global synthesis of 10 CO 2 enrichment experiments reveals that CFE increased with elevation. The satellite‐based EC‐LUE model also demonstrates a positive global elevation‐dependent CFE pattern, albeit substantially weaker than that from experimental observations. Current terrestrial biosphere models, however, could not represent the elevation‐dependent pattern, highlighting the need to improve the representations of plants' elevational physiological adaptation to rising CO 2 in models.

Experimental Study on Suppression and Mechanism of Sloshing Impact Pressure by Vertical Slat Screens Under Broadband Horizontal and Vertical Excitation - Liting Yu; Xiaoqian Luo; Jingcheng Lin; Jie Fan; Heng Jin (Journal of Marine Science and Engineering, 2026)
Sloshing-induced impact pressure is a key damage factor for marine liquid tanks. While research aimed at overcoming screen failure in sloshing suppression under high-frequency excitation has focused on wave height, the dataset of impact pressure remains lacking. Moreover, the pattern of pressure suppression under broadband excitation remains unclear. The primary contribution of this work is the first experimental dataset of impact pressure with vertical slat screens under broadband horizontal and vertical excitation. Second, it reveals pressure suppression patterns by screens across varying excitation frequencies and screen numbers. The results demonstrate that vertical slat screens can effectively suppress pressure. First, screen position matters more than number, proving that suppression is dominated by modal disturbance. Second, wave-height suppression does not reliably represent pressure suppression. Pressure suppression is systematically weaker. An exception occurs under vertical excitation, where pressure suppression can be stronger even when wave-height suppression fails. The results highlight the suppression mechanism dominated by modal disturbance and the instability inherent to parametric sloshing. Wave height, reflecting global potential energy, is effectively suppressed by modal disturbance. Pressure, originating from local kinetic energy, can be effectively suppressed by both modal disturbance and vortex dissipation.

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Modeling water quality in tidal reaches under data-scarce conditions: enhancing aquaculture carrying capacity in bays through upstream contamination control - Fangkun Lin; Zhipeng Luo; Zhiyu Zhang; Jun Chen; Wei Zhang; Lijun Liang; Ghada Eshaq; Xin Yu; Huabin Zeng (Journal of Hydrology, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Synergistic enhancement of Asian monsoons to westerlies intensifies the drying trend of arid Central Asia over the last 20 years - Yu Luo; Changchun Xu; Zhiyi Li; Lin Li; Qian Wang; Qiyue Zhang (Gondwana Research, 2026)

Regulation mechanism of N2O metabolic footprint during the black soldier fly manure composting system amended with biochar, humic acid, and tea residue - Yong He; Yuelin Wang; Nanyi Wang; Wenjuan He; Xiaobing Zhang; Fangying Yu; Jiachao Zhang; Anwei Chen; Renli Qi; Lin Luo; Liuqin He; Xichen Zhao (Environmental Research, 2026)

N, S, P co-doped carbon dots with yellow emission for high-sensitivity detection and bioimaging of α-lipomycin in salt-sensitive hypertension - Xianfeng Wang; Liyuan Meng; Dapeng Zhou; Bingqing Zhao; Yuanhang Yu; Fengwu Lin; Mingzhu Gao; Gongle Shen; Yang Luo (Chemical Engineering Journal, 2026)

Decadal variations in the northern boundary of permafrost in the Xidatan region of the Qinghai-Xizang Plateau: Insights from InSAR and field monitoring - Ju Xin; Luo Jing; Niu Fujun; Yu Fan; Ding Zekun; Yin Guoan; Lin Zhanju; Gao Zeyong (Cold Regions Science and Technology, 2026)

Dl‑3‑n‑Butylphthalide Protects the Blood–Brain Barrier in Neonatal Hypoxic‑Ischemic Brain Damage by Alleviating Endothelial Cell Ferroptosis via the SLC7A11/GSH/GPX4 Pathway - Jiahao Ou; Qianqian Yu; Yuqi Luo; Ming Shen; Jia Lou; Saizhi Jiang; BangMing ye; LiZi Lin; Jianghu Zhu; Zhenlang Lin; Mingchu Fang (Molecular Neurobiology, 2026)

Stable isotopes reveal the evaporation effects during a drought–flood abrupt alternation period in a semiarid river basin in Inner Mongolia, Northwest China - Jian Luo; Chengcheng Xia; Guoqing Wang; Ruihong Yu; Ruizhong Gao; Xiaomin Liu; Ping Miao; Qiuyu Qiao; Junxi Lin (Journal of Hydrology, 2025)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Interfacial work function engineering enables dendrite-free zinc anode and collapse-resistant cathode - Lieyuan Zhang; Bin Xie; Chao Li; Yijia Luo; Xin Tan; Yi Yang; Fengrong Yu; Jianding Li; Yu Huo; Qiaoji Zheng; Shuai Wang; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Genetic analysis of patients with low-frequency non-syndromic hearing loss - Sha Yu; Weitao Li; Xinhao Lin; Liheng Chen; Wenxia Chen; Luo Guo; Yilai Shu (Molecular Genetics and Genomics, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Valve gaping behavior of bivalves under compound marine heatwaves and acidification extremes - Yang Xu; Xin Luo; Yu He; Xiaoning Zang; Weiguo Lin; Yong Liu; Liqiang Zhao (Marine Environmental Research, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Synergistic effects of biochar-microbial inoculants on greenhouse gas mitigation in paddy ecosystems: organic substitution and enzyme driven emission reduction - Kun Zhou; Keqi Zhao; Xiaobing Zhang; Jiachao Zhang; Man Yu; Liuqin He; Lin Luo; Fangying Yu; Lihua Zhang; Xichen Zhao (Biocatalysis and Agricultural Biotechnology, 2025)

Investigation on vehicle emission factors in urban tunnels through mobile measurements with an optimized estimation method - Chaowen Jiang; Chao Lin; Yu Zhao; Zhiwen Luo; Tianyi Zhao (Atmospheric Pollution Research, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

Soil moisture deficits triggered by increasing compound drought and heat events during the growing season in Arid Central Asia - Qian Wang; Changchun Xu; Juncheng Long; Qiyue Zhang; Yu Luo; Lin Li (Journal of Hydrology, 2025)

Carbon-nitrogen-phosphorus level regulation of potentially toxic elements and enzyme activities in paddy soil aggregates: Straw and organic fertilizer effects - Keqi Zhao; Wenbo Xiao; Nanyi Wang; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Anwei Chen; Renli Qi; Fangying Yu; Dan Wan; Lin Luo; et al. (Journal of Environmental Chemical Engineering, 2025)

Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2025)

A generalized chemical kinetics explains heterocyclic amine formation in high-temperature processed meats - Kuen-Yuh Wu; Yu-Hsuan Kuo; Pei-Chen Chao; Yu-Syuan Luo; Wan-Yu Lin; Su-Yin Chiang (Food Chemistry, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Fine root trait dynamics and their relationships with productivity across grasslands under extreme drought - Yuan Shi; Taofeek O. Muraina; Saheed O. Jimoh; Niwu Te; Lin Song; Jiaqi Chen; Hongqiang Wang; Qiang Yu; Xiaoan Zuo; Xingguo Han; Wentao Luo; Scott L. Collins (Oecologia, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Transcriptome analysis revealed that largemouth bass (Micropterus salmoides) may mobilize liver lipid metabolism to provide energy for adaptation to hypertonic stress - Xinxin Wang; Chaoyue Deng; Wenyan Lin; Huapeng Chen; Haoran Yu; Shukui Sun; Junlong Sun; Jian Luo; Feibiao Song (Aquaculture, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Corrigendum to “Soil moisture deficits triggered by increasing compound drought and heat events during the growing season in Arid Central Asia” [J. Hydrol. 660 (2025) 133397] - Qian Wang; Changchun Xu; Juncheng Long; Qiyue Zhang; Yu Luo; Lin Li (Journal of Hydrology, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Biodegradable Janus membrane for oil/water separation and unidirectional oil transport via electrospinning and plasma treatment - Hongshen Lin; Fangxia Yu; Jingxi Liang; Shenao Bai; Rongzong Cai; Pingfan Xu; Peikun Zhang; Yaofa Luo (Journal of Cleaner Production, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Photothermally responsive conductive hydrogels for dual-mode self-sensing soft actuators - Chengnan Qian; Ping Guo; Ruofei Wang; Xuanzi Luo; Yang Yu; Lin Cheng; Aiping Liu (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Electrochemical oxidation of aquaculture wastewater by biogas residue biochar: Effects of chloride and removal of organic pollutants - Xu Pei; Yu Meng; Chengyu Chen; Yongtao Li; Zifeng Luo; Peng Wang; Xiaoqiang Liu; Xueming Lin; Yulong Zhang; Siyi Yang; Zhen Zhang (Biomass and Bioenergy, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Environmental DNA reveals anthropogenic impacts on fish diversity in mountain streams and the increasing risk of species invasion - Yu Zhou; Yunchao Luo; Fan Yu; Zihong Zheng; Jidong Li; Yu Wang; Xu Wang; Jiale Cheng; Zhongqiu Li; Lin Wang; Aichun Xu (Anthropocene, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Performance evaluation of R1336mzz(Z)/TEGDME absorption chiller coupled with low temperature proton exchange membrane fuel cell system - Yufan Yang; Chunhuan Luo; Chunting Zhou; Muran He; Lin Lang; Xi Yu; Changchang Yang; Yufan Chen (International Journal of Refrigeration, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Tetraphenylethene-based covalent organic polymers with tunable Electrochemiluminescence for ultrasensitive detection of tetracycline - Ziqi Lian; Zhoumei Lin; Yu Wang; Li Tan; Wenjing Gao; Yuchan Liu; Huizhen Ma; Junqiang Luo; Chenyao Chen; Wanzhen Chen; Rongkai Ye; Ying Ma; et al. (Food Chemistry, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Herbal dual-network hydrogel: A programmed release for enhanced scarless wound healing - Yiming Lin; Qiang Yu; Ruonan Dong; Chenying Shu; Jiawen Luo; Xiaohong Yuan; Min Lu; Pingbo Xu (Chemical Engineering Journal, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Effects of dietary Inonotus obliquus fermentation products supplementation on meat quality and antioxidant capacity of finishing pigs - Xiangyuan Li; Lin Zhang; Yimin Zhang; Xin Luo; Jiang Yu; Sufang Ren; Laixue Ni; Xianqi Yao; Jiaqiang Wu; Yanwei Mao (Meat Science, 2025)

Corrigendum to “Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils” [Biomass & Bioenergy 197 (2025) 107823] - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

An EXPAR-CRISPR/Cas12a Assay for Rapid Detection of Salmonella - Wensen Lin; Mintao Huang; Hongjian Fu; Luxin Yu; Ying Chen; Lingwei Chen; Yanzhen Lin; Ting Wen; Xiaomin Luo; Yanguang Cong (Current Microbiology, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

Tunning “closed-loop” pockets for constructing stabilized structures of nanobody in the detection of procymidone under a broad range of pH value - Hui-Wei Huang; Aori Qileng; Lin Luo; Yu Wang; Song Huang; Yu-Dong Shen; Min-Ling Liu; Zhen-Lin Xu (Food Chemistry, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Hand preferences in captive non-human primates are associated with generation and stress level - Lin Wang; Yunchao Luo; Haoyu Sun; Yiru Gu; Yu Wang; Yali Bai; Zhongqiu Li (Applied Animal Behaviour Science, 2025)

Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes, 2025)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.

The consequence distance of liquid ammonia release from a pipeline in complex terrain - Lin Teng; Kangkang Wang; Bin Liu; Weidong Li; Pengbo Yin; Zhenchao Li; Xin Huang; Yu Luo; Lilong Jiang (Process Safety and Environmental Protection, 2025)

Microplastics enhance laccase-driven bisphenol A removal in multipollutant wastewater - Jie Zhang; Jiongna Liu; Xinyi Liu; Yu Su; Chunyang Yu; Xuemei Tan; Lin Zhuo; Mei Ye; Qinglin Luo; Biao Li (Journal of Environmental Management, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

Unravelling the response mechanism of extracellular polysaccharides synthesis and salt stress resistance in Tetragenococcus halophilus JY1biofilm formation - Jiayi Lin; Chi Zhao; Jvliang Dai; Yu Zhang; Fangming Lan; Lixin Luo (Food Bioscience, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Temporal trend of organic carbon in the East Siberian Arctic shelf sediments and its relation to the recent climate forcing - Jialong Luo; Li Jiang; Limin Hu; Zenghui Yu; Weini Chong; Fudong Lin; Fenghua Su; Yanguang Liu; Kirill Aksentov; Alexander Bosin; Anatolii Astakhov; Xuefa Shi (Acta Oceanologica Sinica, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Performance of electro-assisted ecological floating bed in antibiotics and conventional pollutants degradation: Mechanisms and microbial response - Liangjing Zhang; Yan Luo; Shucong Lv; Yunlong Liu; Rui Wang; Yu Wang; Kuixuan Lin; Lusan Liu (Journal of Environmental Management, 2025)

Improvement of stability and antioxidant capacity of peptide - iron complexes by sonication - Dong Lin; Yongqing Zhang; Qinqin Xiong; Liyun Zhang; Sha Cheng; Jia Yu; Mashaal Ahmad; Yalin Ni; Su Xu; Heng Luo (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Sustainable and selective upgrade of Cu(II) to High-Value HKUST-1 from acidic electroplating wastewater - Lin Ding; Qiang Wang; Yu Luo; Yunxia Luo; Wei Ren; Hui Shi; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Herry; et al. (Molecular Plant, 2025)

Medicago2035: Genomes, functional genomics, and molecular breeding - Qinyi Ye; Chuanen Zhou; Hao Lin; Dong Luo; Divya Jain; Maofeng Chai; Zhichao Lu; Zhipeng Liu; Sonali Roy; Jiangli Dong; Zeng-Yu Wang; Tao Wang (Molecular Plant, 2025)

GRACE/ML-based analysis of the spatiotemporal variations of groundwater storage in Africa - Kuiyuan Ding; Xiaowei Zhao; Jianmei Cheng; Ying Yu; Yiming Luo; Joaquin Couchot; Kun Zheng; Yihang Lin; Yanxin Wang (Journal of Hydrology, 2025)

Enhancing antibiotic removal of mixed matrix membranes through electrostatic surface segregation of MIL-101(Fe) catalysts - Xia Zheng; Zhaomei Yang; Guangyong Zeng; Qingquan Lin; Xi Chen; Yuan Xiang; Yu-Hsuan Chiao; Ralph Rolly Gonzales; Ze-Xian Low; Jianquan Luo (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Rational design of high-entropy P2/O3 biphasic layered cathodes for enhanced sodium storage performance - Yanfen Wen; Chungang Lin; Hao Shen; Kai Fang; Fupeng Li; Chengkui Luo; Xiaolin Wang; Huilin Peng; Yu Qiao; Shuxin Zhuang; Mi Lu (Chemical Engineering Journal, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Land-atmosphere and ocean–atmosphere couplings dominate the dynamics of agricultural drought predictability in the Loess Plateau, China - Jing Luo; Shengzhi Huang; Yu Wang; Vijay P. Singh; Junguo Liu; Qiang Huang; Guoyong Leng; Ji Li; Haijiang Wu; Xudong Zheng; Wenwen Guo; Xue Lin; et al. (Journal of Hydrology, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Tunnelling-induced nonlinear responses of continuous pipelines resting on tensionless Winkler foundation - Cungang Lin; Zhongjie Wang; Zhongqiang Liu; Xianghuan Luo; Baosong Ma; Yu Chen (Transportation Geotechnics, 2024)

Optimization of degradation conditions for sulfachlorpyridazine by Bacillus sp. DLY-11 and analysis of biodegradation mechanisms - Xiaojun Lin; Jun Zhang; Zifeng Luo; Jingtong Li; Xue Xiao; Xiujuan Wang; Qianyi Cai; Weida Yu; Junshi Tao; Jingwen Zeng; Hongxing Tu; Jinrong Qiu (Journal of Hazardous Materials, 2024)

Low-carbon integrated energy system scheduling considering electric vehicle demand response - Lunjie Wang; Lin Luo; Miao Yu; Xiaodeng Pei (Journal of Cleaner Production, 2024)

Effect of sodium metabisulfite-mediated self-assembly on the quality of silver carp myofibrillar protein-EGCG composite gels - Chenxing Du; Yizhong Shen; Xiyang Zhong; Zhenyu Yu; Shuizhong Luo; Lin Lin; Jianfeng Lu; Zhi Zheng (Food Chemistry, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Interface-Confined nanocatalysts at hollow porous nanofibers for High-Performance cascaded remediation of radioactive wastewater - Qi-Hui Ye; Hao Ye; Yu-Cong Yu; Xiao-Lin Wang; Qiao Luo; Ming-Bang Wu; Juming Yao (Chemical Engineering Journal, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Decreased nitrogen deposition in Beijing over the recent decade and its implications - Ruotong Si; Ziyin Yu; Xin Ma; Zhang Wen; Ting Luo; Wen Xu; Lei Liu; Aohan Tang; Kai Wang; Lin Zhang; Andreas Schweiger; Keith Goulding; et al. (Science of The Total Environment, 2024)

Identifying heavy metal sources and health risks in soil-vegetable systems of fragmented vegetable fields based on machine learning, positive matrix factorization model and Monte Carlo simulation - Jiacheng Shi; Yu Yang; Zhijie Shen; Yuding Lin; Nan Mei; Chengzhong Luo; Yongmin Wang; Cheng Zhang; Dingyong Wang (Journal of Hazardous Materials, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Two-step post-synthetic modification of bipydine-based sp2c-COF for stepwise gold recovery - Bin Zhu; Rengan Luo; Chunyuan Hou; Yuan Gao; Yu Zhang; Kai Wang; Lin Zhang; Jun Luo (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Aflatoxins in dried chilli products in Gansu Province and health risk - Yongjun Li; Haiying Yu; Deng Liu; Shan Luo; Xiangna Gao; Lin Zhang; Jianyun Sun (Food Additives & Contaminants Part B-Surveillance, 2024)

Integration of single-cell and bulk RNA sequencing revealed immune heterogeneity and its association with disease activity in rheumatoid arthritis patients - Xiaofan Mao; Maohua Shi; Beiying Zhang; Rongdang Fu; Mengyun Cai; Sifei Yu; Kairong Lin; Chuling Zhang; Dingru Li; Guoqiang Chen; Wei Luo (Immunologic Research, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Local adaptation of trophic strategy determined the tolerance of coral Galaxea fascicularis to environmental fluctuations - Xiao-Lei Yu; Cheng-Yue Liu; Lei Jiang; Lin-Tao Huang; Yong Luo; Pan Zhang; Yu-Yang Zhang; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Saline-alkali land reclamation boosts topsoil carbon storage by preferentially accumulating plant-derived carbon - Lin Chen; Guixiang Zhou; Biao Feng; Chao Wang; Yu Luo; Fang Li; Congcong Shen; Donghao Ma; Congzhi Zhang; Jiabao Zhang (Science Bulletin, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Habitat differentiation and environmental adaptability contribute to leaf size variations globally in C3 and C4 grasses - Wuchao Gao; Dachuan Dai; Huan Luo; Dongli Yu; Congcong Liu; Ning Zhang; Lin Liu; Chengming You; Shixing Zhou; Lihua Tu; Yang Liu; Congde Huang; et al. (Science of The Total Environment, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

Corrigendum to “The effect of postharvest water migration on metabolism of cassava root by hypobaric storage” [Innovative Food Science and Emerging Technologies, 93 (May 2024)103609] - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Efficient and selective upgrading of biomass-derived furfural into 1,5 pentanediol by Co2+ etched ZIF-8 derived ZnCo layered double hydroxides nanoflake - Ye Tian; Wenlong Xie; Zihao Yang; Zhendong Yu; Renjie Huang; Lin Luo; Miao Zuo; Zheng Li; Lu Lin; Xianhai Zeng (Chemical Engineering Journal, 2024)

Recent rapid initiation and growth of retrogressive thaw slumps in the Hoh Xil region of the Qinghai-Tibetan Plateau - Jing Luo; Fan Yu; Fujun Niu; Miaomiao Yao; Zhanju Lin; Minghao Liu; Guoan Yin; Zeyong Gao (CATENA, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Insights into the role of endogenous humic acid on antibiotics bioadsorption process in wastewater: Mechanisms and potential implications - Lin Qiang; Luo Ancheng; Yu Chisheng; Chen Kaiying; Yasir Hamid; Liang Zhiwei; Wang Yunlong; Yang Wenchen (Journal of Water Process Engineering, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Sub-inhibitory concentrations of tetrabromobisphenol A induce the biofilm formation of methicillin-resistant Staphylococcus aureus - Guofang Yu; Huimin Xi; Tianle Sheng; Jin Lin; Zhaoxia Luo; Jianqing Xu (Archives of Microbiology, 2024)

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Occurrence of micropollutants in rural domestic wastewater in Zhejiang Province, China and corresponding wastewater-based epidemiology analysis - Lin Qiang; Yu Chisheng; Chen Kaiyin; Yasir Hamid; Luo Ancheng; Liang Zhiwei; Xu Tianyu (Science of The Total Environment, 2024)

Soil moisture dynamics and associated rainfall-runoff processes under different land uses and land covers in a humid mountainous watershed - Zhixin Lin; Qiang Wang; Youpeng Xu; Shuang Luo; Caiyu Zhou; Zhihui Yu; Chong-Yu Xu (Journal of Hydrology, 2024)

Hidden danger: The long-term effect of ultrafine particles on mortality and its sociodemographic disparities in New York State - Quan Qi; Fangqun Yu; Arshad A. Nair; Sam S.S. Lau; Gan Luo; Imran Mithu; Wangjian Zhang; Sean Li; Shao Lin (Journal of Hazardous Materials, 2024)

Improving cotton productivity and nitrogen use efficiency through late nitrogen fertilization: Evidence from a three-year field experiment in the Xinjiang - Yu Tian; Feng Shi; Xiaojuan Shi; Humei Zhang; Zemin Li; Hairong Lin; Honghai Luo; Karine Chenu (Field Crops Research, 2024)

Microbial strategies for effective hexavalent chromium removal: A comprehensive review - Shilin Zha; Ao Yu; Zhongbing Wang; Qi Shi; Xunniu Cheng; Chunli Liu; Chunjian Deng; Guisheng Zeng; Shenglian Luo; Zongwen Zhao; Lin Zhou (Chemical Engineering Journal, 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Landscape and risk assessment of microplastic contamination in farmed oysters and seawater along the coastline of China - Huai Lin; Xin Li; Wenjin Hu; Shenbo Yu; Xi Li; Liusheng Lei; Fengxia Yang; Yi Luo (Journal of Hazardous Materials, 2024)

The effect of postharvest water migration on metabolism of cassava root by hypobaric storage - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

SCREENES: Enhancing non-uniform sampling reconstruction for symmetrical NMR spectroscopy - Ze Fang; Bo Chen; Chengda Huang; Yifei Yuan; Yao Luo; Liubin Wu; Yida Chen; Yuqing Huang; Yu Yang; Enping Lin; Zhong Chen (Analytica Chimica Acta, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Effects of polystyrene microplastics on the metabolic level of Pseudomonas aeruginosa - Hui Tao; Lingqin Zhou; Duo Yu; Yiyang Chen; Yunxin Luo; Tao Lin (Science of The Total Environment, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

A flexible wearable phase change composite with electro-/photo-thermal heating for personal thermal management and human body motion detection - Tianwen Luo; Lingli Kong; Luji Li; Junjie Lu; Zhiyu Yu; Baofeng Lin; Lihua Fu; Chuanhui Xu (Chemical Engineering Journal, 2024)

Heteroatom doping-induced Pt dispersion and electronic effect for boosting the catalytic performance in the hydrogenation of nitrobenzene to p-aminophenol - Chong Yao; Jiwei Wu; Limei Pan; Lu Yu; Jie Luo; Jinjin Shan; Jie Liu; Chunshan Lu; Feng Feng; Xiaoliang Xu; Lili Lin; Yuxue Yue; et al. (Chemical Engineering Journal, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Novel insights into aerobic 17β-estradiol degradation by enriched microbial communities from mangrove sediments - Shan Zhang; Xueying Ye; Xianbin Lin; Xiangwei Zeng; Shanshan Meng; Wenqi Luo; Fei Yu; Tao Peng; Tongwang Huang; Jin Li; Zhong Hu (Journal of Hazardous Materials, 2024)

Multiphase flow and reactor optimization of a 1MWth pilot-scale circulating fluidized bed for coal staged conversion - Yuxin Ge; Jiahui Yu; Junjie Lin; Shuai Wang; Kun Luo; Qinhui Wang; Jianren Fan (Chemical Engineering Journal, 2024)

A new Cd(II) Complex: Fluorescence Performances, Loading with Budesonide-hydrogels on Pediatric Asthma and Molecular Docking - Lu Luo; Siming Gong; Lin Lei; Xin Yu; Shimin Zhong (Journal of Fluorescence, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Process-based evaluation of carbon emissions from the on-site construction of prefabricated steel structures: A case study of a multistory data center in China - Zujian Huang; Hao Zhou; Hao Tang; Deyin Zhang; Yang Zhao; Juan Yu; Minjie Luo; Yicheng Wang; Borong Lin (Journal of Cleaner Production, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Rare 7,9′-dinorlignans with neuroprotective activity from the roots of Lindera aggregata (Sims) Kosterm - Qian-Qing Liu; Lin-An Xiong; Jia-Yu Qian; Ting-Ting Gong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Effects of elevated temperature and copper exposure on the physiological state of the coral Galaxea fascicularis - Meng Cheng; Yong Luo; Xiao-Lei Yu; Lin-Tao Huang; Jian-Sheng Lian; Hui Huang (Marine Environmental Research, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Identifying changes in flood characteristics and their causes from an event-based perspective in the Central Taihu Basin - Shuang Luo; Qiang Wang; Youpeng Xu; Zhixin Lin; Zhihui Yu (Science of The Total Environment, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

Environmental exposure disparities in ultrafine particles and PM2.5 by urbanicity and socio-demographics in New York state, 2013–2020 - Arshad Arjunan Nair; Shao Lin; Gan Luo; Ian Ryan; Quan Qi; Xinlei Deng; Fangqun Yu (Environmental Research, 2023)

Partial denitrification-anammox granular sludge domesticated from high-strength anammox granules and the high-efficiency performance in treating low-nitrogen wastewater - Lan Lin; Zibin Luo; Yanlong Zhang; Yuanyuan Ren; Yu-You Li (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Role of feeding and physiological trade-offs in sustaining resilience of the coral Galaxea fascicularis to light limitation - Xiao-Lei Yu; Lei Jiang; Yong Luo; Cheng-Yue Liu; Yu-Yang Zhang; Lin-Tao Huang; Pan Zhang; Xiang-Cheng Yuan; Hui Huang (Coral Reefs, 2023)

Exploring an intelligent adaptation method of hydrological model parameters for flood simulations based on the light gradient-boosting machine - Kangling Lin; Sheng Sheng; Hua Chen; Yanlai Zhou; Yuxuan Luo; Lihua Xiong; Shenglian Guo; Chong-Yu Xu (Journal of Hydrology, 2023)

Smart enzyme-free amplification dual-mode self-powered platform designed on two-dimensional networked graphdiyne and DNA nanorods for ultra-sensitive detection of breast cancer biomarkers - Yunzhi Ma; Jinyue Shi; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Dual application of Tribonema sp. GXU-A10 for purifying molasses vinasse and promoting the growth and health of Oreochromis niloticus - Hong-Yu Deng; Yue-Xin Sun; Xin-Qiang Chen; Yu Jiang; Wan-Lin Gu; Luo-Dong Huang; Pei-Hong Shen (Algal Research, 2023)

Contrasting laboratory and field outcomes of bat–moth interactions - Aiqing Lin; Jiqian Li; Yinli Hu; Maojun Zhong; Minglun Yu; Nina Ma; Tingting Wei; Jinhong Luo; Jiang Feng (Molecular Ecology, 2023)
Predator–prey interactions are important but difficult to study in the field. Therefore, laboratory studies are often used to examine the outcomes of predator–prey interactions. Previous laboratory studies have shown that moth hearing and ultrasound production can help prey avoid being eaten by bats. We report here that laboratory behavioural outcomes may not accurately reflect the outcomes of field bat–moth interactions. We tested the success rates of two bat species capturing moths with distinct anti‐bat tactics using behavioural experiments. We compared the results with the dietary composition of field bats using next‐generation DNA sequencing. Rhinolophus episcopus and Rhinolophus osgoodi had a lower rate of capture success when hunting for moths that produce anti‐bat clicks than for silent eared moths and earless moths. Unexpectedly, the success rates of the bats capturing silent eared moths and earless moths did not differ significantly from each other. However, the field bats had a higher proportion of silent eared moths than that of earless moths and that of clicking moths in their diets. The difference between the proportions of silent eared moths and earless moths in the bat diets can be explained by the difference between their abundance in bat foraging habitats. These findings suggest that moth defensive tactics, bat countertactics and moth availability collectively shape the diets of insectivorous bats. This study illustrates the importance of using a combination of behavioural experiments and molecular genetic techniques to reveal the complex interactions between predators and prey in nature.

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

Network structure and stability of the river connectivity in a rapidly urbanizing region - Zhihui Yu; Miao Lu; Youpeng Xu; Qiang Wang; Zhixin Lin; Shuang Luo (Science of The Total Environment, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

A highly sensitive self-powered sensing method designed on DNA circuit strategy and MoS2 hollow nanorods for detection of thalassemia - Jinyue Shi; Danyao Tang; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Exploring a similarity search-based data-driven framework for multi-step-ahead flood forecasting - Kangling Lin; Hua Chen; Yanlai Zhou; Sheng Sheng; Yuxuan Luo; Shenglian Guo; Chong-Yu Xu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

Exploring a multi-output temporal convolutional network driven encoder-decoder framework for ammonia nitrogen forecasting - Sheng Sheng; Kangling Lin; Yanlai Zhou; Hua Chen; Yuxuan Luo; Shenglian Guo; Chong-Yu Xu (Journal of Environmental Management, 2023)

A strategy for regulation of gas–liquid microflow patterns by changing gas kinetic energy - Lin Sheng; Yu Chang; Junjie Wang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

Cation-deficient perovskite Sr1-xTi1-yNiyO3-δ anodes with in-situ exsolution of Ni nanoparticles for direct ammonia solid oxide fuel cells - Fulan Zhong; Lei Wang; Huihuang Fang; Yu Luo; Chongqi Chen; Li Lin; Kongfa Chen; Lilong Jiang (Chemical Engineering Journal, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Broad spectral photodetectors based on BiOCl@boronate polymer core-shell heterojunctions - Wenkang Wei; Haiyan Zuo; Yu Luo; Chunying Yang; Hailong Chen; Liu He; Haimen Lin; Guorong Chen; Weiang Luo; Birong Zeng; Yiting Xu; Conghui Yuan; et al. (Chemical Engineering Journal, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

miR-4299 inhibits tumor progression in pancreatic cancer through targeting ADAM17 - Junhong Liu; Lin Ye; Kangqiang Lin; Tieshan Zhong; Jiguang Luo; Tao Wang; Liya Suo; Qingrong Mo; Shuqun Li; Qian Chen; Yaqun Yu (Molecular and Cellular Biochemistry, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Exploring distinct types of intertidal bars on either side of a small estuary using a multifaceted approach - Ke Luo; Yunwei Wang; Li Wang; Hangjie Lin; Jie Qin; Dongmei Xie; Burghard Flemming; Shu Gao; Qian Yu (Marine Geology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Evaluation of key factors influencing urban ozone pollution in the Pearl River Delta and its atmospheric implications - Xiao-Yu Lin; Shi-Yong Xia; Yao Luo; Heng-Xiao Han; Ling-Yan He (Atmospheric Environment, 2023)

Are the extreme marine heatwave events in the central-eastern tropical Pacific predictable 30–60 days in advance by NUIST CFS1.1 model? - Lin Lin; Yueyue Yu; Chuhan Lu; Jingjia Luo; Lin Chen; Jing Ma; Zhaoyong Guan; Jiye Wu (Atmospheric Research, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

MiR-370-3p aggravates blood–brain barrier injury and neuron apoptosis by targeting SMURF1 to activate the TLR4/MyD88/NF-κB signaling in sepsis-associated encephalopathy - Neng Wang; Dan Zhong; Jie Lin; Mei Ye; Yu Chen; Lili Wang; Mei Chen; Cong Luo (Molecular & Cellular Toxicology, 2023)

Semi-analytical solutions of three-dimensional ground movements due to shallow tunnelling - Lin Yu; Dingli Zhang; Qian Fang; Tong Xu; Jiwei Luo; Wenbo Chen (Tunnelling and Underground Space Technology, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

New insights into differential salinity tolerance between autotrophic and heterotrophic partial nitrification - Lin Qiang; Wang Yunlong; Yu Chisheng; Luo Ancheng; Liang Zhiwei (Journal of Environmental Chemical Engineering, 2023)

Ultralow Ru loading RuO2-TiO2 with strong oxide-support interaction for efficient chlorine evolution and ammonia-nitrogen-elimination - Mengchen Hu; Tianqi Yu; Kexin Tan; Anchao Zhou; Lin Luo; Shibin Yin (Chemical Engineering Journal, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Metabolomics reveals size-dependent persistence and reversibility of silver nanoparticles toxicity in freshwater algae - Lin Shen; Qin Qin Li; Yu Hang Kang; Qian Qian Xiang; Xia Luo; Li Qiang Chen (Aquatic Toxicology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Binding, activity and risk assessment of bisphenols toward farnesoid X receptor pathway: In vitro and in silico study - Donghui Zhang; Xinya Liu; Yuan Qi; Yongfeng Lin; Kunming Zhao; Yuan Jin; Jiao Luo; Lin Xu; Dianke Yu; Chuanhai Li (Science of The Total Environment, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

First evidence and potential sources of novel brominated flame retardants and BDE 209 in the deepest ocean - Jingqian Xie; Gaoxin Zhang; Qiang Wu; Min Luo; Duofu Chen; Yu Zhang; Lisheng He; Yingming Li; Qinghua Zhang; Tian Lin; Guibin Jiang (Journal of Hazardous Materials, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Biosensors for detection of paralytic shellfish toxins: Recognition elements and transduction technologies - Liu-Na Wei; Lin Luo; Bing-Zhi Wang; Hong-Tao Lei; Tian Guan; Yu-Dong Shen; Hong Wang; Zhen-Lin Xu (Trends in Food Science & Technology, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

Nanoporous electrode with stable polydimethylsiloxane coating for direct electrochemical analysis of bisphenol A in complex wine media - Jingjing Wang; Jiening Yu; Yuan Yu; Zisheng Luo; Gangfeng Li; Xingyu Lin (Food Chemistry, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Low-crystalline Ni(OH)2 ultrathin nanosheets upcycled from solid wastes for efficient photoconversion of low-concentration CO2 - Bin Han; Yuanfang Lin; Yu Luo; Weizhen Liu; Xueming Liu; Zonglin Weng; Xinwen Ou; Zhang Lin (Chemical Engineering Journal, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

A Novel Variable Weight VIKOR Grade Assessment Method for Waterway Navigation Safe Routes Selection - Gao-Feng Yu; Yu-Jin Lin; Xiao-Mei Luo (Journal of Marine Science and Engineering, 2023)
According to the characteristics of waterway navigation safe routes selection, and considering the individual feelings and group benefits of information, as well as no-compensation information between indexes, this paper describes the safe rating of waterway navigation routes, and then puts forward an evaluation model of and method for waterway navigation safe route selection based on variable weight VIKOR. First of all, from the concept and connotation of grade assessment, this paper describes the safe rating of waterway navigation routes, so as to avoid confusing the two essential different problems of safe rating and ranking. Then, the evaluation indexes and membership function of the appropriate grade of the safe rating of waterway navigation route are constructed, and the weights of an evaluation index based on entropy are proposed. Secondly, a variable weight VIKOR evaluation model and a binary semantic evaluation method for the safe grading of waterway navigation safe routes are proposed. Finally, through case study and comparative analysis, the rationality and feasibility of the model and method proposed in this paper are illustrated. This model can better reflect the connotation and characteristics of the appropriate grade assessment of waterway navigation safe routes, and provides new approaches and methods to support the development and management of waterway navigation safe route selection.

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Using a human bronchial epithelial cell-based malignant transformation model to explore the function of hsa-miR-200 family in the progress of PM2.5-induced lung cancer development - Wanli Ma; Lin Xu; Xueying Sun; Yuan Qi; Shen Chen; Daochuan Li; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Jiao Luo; Chuanhai Li; Kunming Zhao; et al. (Environmental Pollution, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Hydrodynamics and mass transfer performance of gas–liquid microflow in viscous liquids - Lin Sheng; Yu Chang; Jian Deng; Guangsheng Luo (Chemical Engineering Journal, 2023)

Hierarchical multiphase (Ni, Co)-Se with adjustable interlayer distance derived from reconstructed ZIF-L for enhanced hybrid-supercapacitors - Lin Sun; Yu Liu; Bifu Luo; Fangrong Yan; Xiaoying Liu; Fangfang Zhu; Weidong Shi (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Identification of high-concern organic pollutants in tap waters from the Yangtze River in China based on combined screening strategies - Liben Chou; Chengzhuo Zhou; Wenrui Luo; Jing Guo; Yanhong Shen; Die Lin; Chang Wang; Hongxia Yu; Xiaowei Zhang; Si Wei; Wei Shi (Science of The Total Environment, 2023)

Ultrafast and absolute quantification of SARS-CoV-2 on food using hydrogel RT-LAMP without pre-lysis - Tao Yang; Dong Li; Yuhua Yan; Fatima-ezzahra Ettoumi; Ricardo A. Wu; Zisheng Luo; Hanry Yu; Xingyu Lin (Journal of Hazardous Materials, 2023)

Cation-doped V2O5 microsphere as a bidirectional catalyst to activate sulfur redox reactions for lithium-sulfur batteries - Fan-Jun Liu; Wen-Lin Luo; Ze Zhang; Ji Yu; Jian-Xin Cai; Zhen-Yu Yang (Chemical Engineering Journal, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

CREB1 contributes colorectal cancer cell plasticity by regulating lncRNA CCAT1 and NF-κB pathways - Bin Li; Lisi Zheng; Jiayi Ye; Chenmin Zhang; Jie Zhou; Qiaojuan Huang; Yanhua Guo; Luqin Wang; Peng Yu; Shurong Liu; Qiao Lin; Yuxia Luo; et al. (Science China Life Sciences, 2022)

Transformation of HBCDs by Rhodococcus sp. stu-38 - Fei Yu; Wenqi Luo; Yuyang Li; Shanshan Meng; Xianbin Lin; Lele Li; Xueying Ye; Hui Wang; Tao Peng; Tongwang Huang; Zhong Hu (Current Microbiology, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Distinct Evolution of the SST Anomalies in the Far Eastern Pacific between the 1997/98 and 2015/16 Extreme El Niños - Shaolei Tang; Jing-Jia Luo; Lin Chen; Yongqiang Yu (Advances in Atmospheric Sciences, 2022)

Short-term variations and influencing factors of suspended sediment concentrations at the Heisha Beach, Guangdong, China - Jintang Ou; Haoyan Dong; Liangwen Jia; Xiangxin Luo; Zixiao He; Kanglin Chen; Jing Liu; Yitong Lin; Mingdong Yu; Mingen Liang (Acta Oceanologica Sinica, 2022)

Environmental Regulation of Photosynthetically Produced Dissolved Organic Carbon by Phytoplankton Along a Subtropical Estuarine Bay - Jianhua Kang; Zhaohe Luo; Hala. F. Mohamed; Yili Lin; Shuhong Huang; Yu Wang; Wenlu Lan (Frontiers in Marine Science, 2022)
Photosynthetically produced dissolved organic carbon (PDOC) released by marine phytoplankton has an important significance on the marine carbon cycle and on the growth of heterotopic bacteria (HB). However, PDOC is often neglected in the estimation of global marine primary productivity and carbon sequestration capacity. This work studied the issue of PDOC and its environmental regulation mechanism through field investigation and lab experiments in an estuarine bay during southwest and northeast monsoon. We used the percentage of extracellular release (PER) as a key indicator to evaluate the contribution of PDOC to total primary productivity (TPP). We also compared PER among different seasons and sectors and then analyzed the inter-relationship between PDOC and bacterial carbon demand (BCD), size-fractionated phytoplankton, bacterial production (BP), and TPP. We finally discussed the impact factors of PDOC productivity. The results showed that the average contribution of PDOC to TPP in Qinzhou bay could reach 15% during two seasons, which satisfies about 25% of the carbon requirement by HB in the bay. Multiple factors contribute to the seasonal (SW monsoon 13% < NE monsoon 18%) and sectoral variation (outer bay 26% > middle bay 17% > inner bay 7%) in PER, the most significant of which are salinity and nitrogen to phosphorus ratios. PER is also related to phytoplankton community structure and nutrient limitation, the higher PER in the outer bay is attributed to the dual effect of picophytoplankton being the predominant species and a severe imbalance in the nitrogen to phosphorus ratio, both of which lead to increased phytoplankton PDOC release. On the other hand, the lower PER in the inner bay was mainly due to the dominance of microphytoplankton and nitrogen to phosphorus ratio which is close to the redfield ratio. There is still a non-uniform conclusion on the relationship between PER and TPP, suggesting that this relationship needs to be evaluated not only in a horizontal-independent way but also through seasonal and vertical dimensions. The non-linear relationship between PDOC and BCD found in this study potentially indicated weak coupling between phytoplankton exudation and bacterial metabolism. In addition to phytoplankton exudate, HB is still dependent on other sources of DOC to meet their carbon requirements.

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

Consistent responses of microbial C and N metabolic processes to elevated CO2 across global terrestrial ecosystems - Jiahui Lin; Yanlan Huang; Haochun Zhao; Mengjie Yu; Weiqin Su; Huaihai Chen; Peng Leng; Jihui Li; Yu Luo; Yong Li; Zhongmin Dai; Jianming Xu (Journal of Soils and Sediments, 2022)

Identifying the priority areas for enhancing the ecosystem services in hilly and mountainous areas of southern China - Jia-ling Tian; Yu Peng; Yi-hang Huang; Ting Bai; Lian-lin Liu; Xiao-ao He; Shi-qian Luo (Journal of Mountain Science, 2022)

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

The relationship between anthocyanin accumulation and photoprotection in young leaves of two dominant tree species in subtropical forests in different seasons - Zheng-Chao Yu; Wei Lin; Xiao-Ting Zheng; Wah Soon Chow; Yan-Na Luo; Min-Ling Cai; Chang-Lian Peng (Photosynthesis Research, 2021)

Activation of Ca2+/Calmodulin-Dependent Protein Kinase II (CaMKII) with Lidocaine Provokes Pyroptosis of Glioblastoma Cells - B. Zhou; Y. Lin; S. Chen; J. Cai; Z. Luo; S. Yu; J. Lu (Bulletin of Experimental Biology and Medicine, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Diversity of Diaporthe species associated with melanose disease on citrus trees in Jiangxi Province, China - Zhe-Zheng Zeng; Chingchai Chaisiri; Xiang-Yu Liu; Yang Lin; Chao-Xi Luo (European Journal of Plant Pathology, 2021)

The effects of dark treatment on photosynthesis and growth in young and mature leaves of Syzygium rehderianum - ZhengChao Yu; Wei Lin; XiaoTing Zheng; YanNa Luo; ChangLian Peng (Brazilian Journal of Botany, 2021)

Amygdala-based Functional Network Reveals Dissociated Neural Correlates of Consensual and Idiosyncratic Emotional Movie Experiences - Lin Cui; Bingbing Guo; Dan Zhao; Jiaxin Li; Yu Luo; Ming Meng (Neuroscience Bulletin, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Projections from Infralimbic Cortex to Paraventricular Thalamus Mediate Fear Extinction Retrieval - Yan Tao; Cheng-Yun Cai; Jia-Yun Xian; Xiao-Lin Kou; Yu-Hui Lin; Cheng Qin; Hai-Yin Wu; Lei Chang; Chun-Xia Luo; Dong-Ya Zhu (Neuroscience Bulletin, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Multifunctional Role of Polyvinylpyrrolidone in Pharmaceutical Formulations - Yu Luo; Yanlong Hong; Lan Shen; Fei Wu; Xiao Lin (AAPS PharmSciTech, 2021)

Effects of high-intensity interval training on gut microbiota profiles in 12 months’ old ICR mice - Guiping Wang; Huanhuan Zhou; Lin Zhang; Ruyi Li; Li Luo; Zengli Yu; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2020)

Shifts in the bacterial community along with root-associated compartments of maize as affected by goethite - Peduruhewa H Jeewani; Lin Chen; Lukas Van Zwieten; Congcong Shen; Georg Guggenberger; Yu Luo; Jianming Xu (Biology and Fertility of Soils, 2020)

Ancestral niche separation and evolutionary rate differentiation between sister marine flavobacteria lineages - Chun‐Xu Xue; Hao Zhang; He‐Yu Lin; Ying Sun; Danli Luo; Yongjie Huang; Xiao‐Hua Zhang; Haiwei Luo (Environmental Microbiology, 2020)
Summary Marine flavobacteria are specialists for polysaccharide degradation. They dominate in habitats enriched with polysaccharides, but are also prevalent in pelagic environments where polysaccharides are less available. These niches are likely occupied by distinct lineages, but evolutionary processes underlying their niche differentiation remain elusive. Here, genomic analyses and physiological assays indicate that the sister flavobacteria lineages Leeuwenhoekiella and Nonlabens likely explore polysaccharide‐rich macroalgae and polysaccharide‐poor pelagic niches respectively. Phylogenomic analyses inferred that the niche separation likely occurred anciently and coincided with increased sequence evolutionary rate in Nonlabens compared with Leeuwenhoekiella . Further analyses ruled out the known mechanisms likely driving evolutionary rate acceleration, including reduced selection efficiency, decreased generation time and increased mutation rate. In particular, the mutation rates were determined using an unbiased experimental method, which measures the present‐day populations and may not reflect ancestral populations. These data collectively lead to a new hypothesis that an ancestral and transient mutation rate increase resulted in evolutionary rate increase in Nonlabens . This hypothesis was supported by inferring that gains and losses of genes involved in SOS response, a mechanism known to drive transiently increased mutation rate, coincided with evolutionary rate acceleration. Our analyses highlight the evolutionary mechanisms underlying niche differentiation of flavobacteria lineages.

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

The power of habit: does production experience lead to pesticide overuse? - Yanzhong Huang; Xiaofeng Luo; Lin Tang; Weizhen Yu (Environmental Science and Pollution Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Effect of slope gradient on the subsurface water flow velocity of sand layer profile - Zhen Han; Xiao-yan Chen; Yu-han Huang; Bang-lin Luo; Hang Xing; Yong-chao Huang (Journal of Mountain Science, 2020)

LLCLPLDA: a novel model for predicting lncRNA–disease associations - Guobo Xie; Shuhuang Huang; Yu Luo; Lei Ma; Zhiyi Lin; Yuping Sun (Molecular Genetics and Genomics, 2019)

Carbon-based magnetic nanocomposite as catalyst for persulfate activation: a critical review - Ya Pang; Kun Luo; Lin Tang; Xue Li; Jiangfang Yu; Junyuan Guo; Yuanyuan Liu; Zhu Zhang; Ran Yue; Ling Li (Environmental Science and Pollution Research, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

Quantitative climatic reconstruction of the Last Glacial Maximum in China - Haibin Wu; Qin Li; Yanyan Yu; Aizhi Sun; Yating Lin; Wenqi Jiang; Yunli Luo (Science China Earth Sciences, 2019)

Neuroligins Differentially Mediate Subtype-Specific Synapse Formation in Pyramidal Neurons and Interneurons - Qiang-Qiang Xia; Jing Xu; Tai-Lin Liao; Jie Yu; Lei Shi; Jun Xia; Jian-Hong Luo; Junyu Xu (Neuroscience Bulletin, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

Contrastive removal of oxytetracycline and chlortetracycline from aqueous solution on Al-MOF/GO granules - Lin-ling Yu; Zi-fen Luo; Ying-ying Zhang; Shi-chuan Wu; Cao Yang; Jian-hua Cheng (Environmental Science and Pollution Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Metatranscriptome analysis reveals environmental and diel regulation of a Heterosigma akashiwo (raphidophyceae) bloom - Nanjing Ji; Lingxiao Lin; Ling Li; Liying Yu; Yaqun Zhang; Hao Luo; Meizhen Li; Xinguo Shi; Da‐Zhi Wang; Senjie Lin (Environmental Microbiology, 2018)
Summary Despite numerous laboratory studies on physiologies of harmful algal bloom (HAB) species, physiologies of these algae during a natural bloom are understudied. Here, we investigated a bloom of the raphidophyte Heterosigma akashiwo in the East China Sea in 2014 using metabarcode (18S rDNA) and metatranscriptome sequencing. Based on 18S rDNA analyses, the phytoplankton community shifted from high diversity in the pre‐bloom stage to H. akashiwo predominance during the bloom. A sharp decrease in ambient dissolved inorganic phosphate and strong up‐regulation of phosphate and dissolved organic phosphorus (DOP) uptake genes, including the rarely documented (ppGpp)ase, in H. akashiwo from pre‐bloom to bloom was indicative of rapid phosphorus uptake and efficient utilization of DOP that might be a driver of the H. akashiwo bloom. Furthermore, observed up‐regulated expression of mixotrophy‐related genes suggests potential contribution of mixotrophy to the bloom. Accelerating photosynthetic carbon fixation was also implied by the up‐regulation of carbonic anhydrase genes during the bloom. Notably, we also observed a strong morning‐to‐afternoon shift in the expression of many genes. Our findings provide insights into metabolic processes likely important for H. akashiwo bloom formation, and suggest the need to consider timing of sampling in field studies on this alga.

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Dcf1 Triggers Dendritic Spine Formation and Facilitates Memory Acquisition - Qiang Liu; Ruili Feng; Yu Chen; Guanghong Luo; Huang Yan; Ling Chen; Rongfei Lin; Yuqiang Ding; Tieqiao Wen (Molecular Neurobiology, 2018)

Does repeated biochar incorporation induce further soil priming effect? - Yu Luo; Qimei Lin; Mark Durenkamp; Yakov Kuzyakov (Journal of Soils and Sediments, 2018)

The topological organization of white matter network in internet gaming disorder individuals - Jinquan Zhai; Lin Luo; Lijun Qiu; Yongqiang Kang; Bo Liu; Dahua Yu; Xiaoqi Lu; Kai Yuan (Brain Imaging and Behavior, 2017)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

Increased Src Family Kinase Activity Disrupts Excitatory Synaptic Transmission and Impairs Remote Fear Memory in Forebrain Shp2-Deficient Mice - Xunyi Yan; Bin Zhang; Wen Lu; Lin Peng; Qian Yang; Wei Cao; Shen Lin; Wenyue Yu; Xiaoming Li; Yuehai Ke; Shengtian Li; Wei Yang; et al. (Molecular Neurobiology, 2017)

Quantifying soil macropore networks in different forest communities using industrial computed tomography in a mountainous area of North China - Chen Meng; Jianzhi Niu; Xiang Li; Ziteng Luo; Xiaoqing Du; Jie Du; Xingna Lin; Xinxiao Yu (Journal of Soils and Sediments, 2017)

Soil priming effects following substrates addition to biochar-treated soils after 431 days of pre-incubation - Yu Luo; Qimei Lin; M. Durenkamp; A. J. Dungait; P. C. Brookes (Biology and Fertility of Soils, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

A sensitive duplex nanoparticle-assisted PCR assay for identifying porcine epidemic diarrhea virus and porcine transmissible gastroenteritis virus from clinical specimens - Yu Zhu; Lin Liang; Yakun Luo; Guihua Wang; Chunren Wang; Yudong Cui; Xia Ai; Shangjin Cui (Virus Genes, 2017)

The effects of combinations of biochar, lime, and organic fertilizer on nitrification and nitrifiers - Kaile Zhang; Lin Chen; Yong Li; Philip C. Brookes; Jianming Xu; Yu Luo (Biology and Fertility of Soils, 2017)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Ground-based radar reflectivity mosaic of mei-yu precipitation systems over the Yangtze River–Huaihe River basins - Yali Luo; Weimiao Qian; Yu Gong; Hongyan Wang; Da-Lin Zhang (Advances in Atmospheric Sciences, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Trabala Vishnou Gigantina Yang (Lepidoptera: Lasiocampidae) Larval Fitness on six Sympatric Plant Species in Sea-Buckthorn Forest - Dong-Mei Wen; Lin-Feng Yu; Yong-Hua Liu; Xiong-Fei Yan; Peng-Fei Lu; You-Qing Luo (Journal of Insect Behavior, 2016)

The relationships of meteorological factors and nutrient levels with phytoplankton biomass in a shallow eutrophic lake dominated by cyanobacteria, Lake Dianchi from 1991 to 2013 - Qichao Zhou; Yunlin Zhang; Dunmei Lin; Kun Shan; Yu Luo; Lei Zhao; Zhiwei Tan; Lirong Song (Environmental Science and Pollution Research, 2016)

Molecular diversity of microbial eukaryotes in sea water from Fildes Peninsula, King George Island, Antarctica - Wei Luo; Huirong Li; Shengquan Gao; Yong Yu; Ling Lin; Yinxin Zeng (Polar Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Sex difference of autosomal alleles in populations of European and African descent - Lingjun Zuo; Tong Wang; Xiandong Lin; Jijun Wang; Yunlong Tan; Xiaoping Wang; Xueqing Yu; Xingguang Luo (Genes & Genomics, 2015)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Expression Analysis and Binding Assays in the Chemosensory Protein Gene Family Indicate Multiple Roles in Helicoverpa armigera - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Jing Zhu; Jin-Jie Cui; Shuang-Lin Dong (Journal of Chemical Ecology, 2015)

Systemic nematicidal activity and biocontrol efficacy of Bacillus firmus against the root-knot nematode Meloidogyne incognita - Jing Xiong; Qiaoni Zhou; Haiyan Luo; Liqiu Xia; Lin Li; Ming Sun; Ziquan Yu (World Journal of Microbiology and Biotechnology, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Development and characterization of 13 novel microsatellite loci in a threatened reef fish, humpback grouper (Cromileptes altivelis) - Yu Wang; Guohua Chen; Feng Yan; Haoran Lin; Jian Luo (Conservation Genetics Resources, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

First report on the allelopathic effect of Tychonema bourrellyi (Cyanobacteria) against Microcystis aeruginosa (Cyanobacteria) - Jihai Shao; Liang Peng; Si Luo; Gongliang Yu; Ji-dong Gu; Shen Lin; Renhui Li (Journal of Applied Phycology, 2013)

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening - Jing-Hua Sun; Jing-Jing Luo; Lin Tian; Chun-Li Li; Yu Xing; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2013)

Genetic variation in the Nrf2 promoter associates with defective spermatogenesis in humans - Bolan Yu; Huanlan Lin; Lixia Yang; Kang Chen; Haihua Luo; Jianqiao Liu; Xingcheng Gao; Xuefeng Xia; Zhaofeng Huang (Journal of Molecular Medicine, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

Regional sea level change in Northwest Pacific: Process, characteristic and prediction - Wen Luo; Linwang Yuan; Zhaoyuan Yu; Lin Yi; Zhiren Xie (Journal of Geographical Sciences, 2011)

Candida tropicalis: characterization of a strain capable of degrading high concentrations of phenol - Liming Wang; Yanwen Lin; Linyan Yang; Ping Yu; Zhixiong Xie; Yunbai Luo (Biotechnology Letters, 2011)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Life cycle assessment of switchgrass-derived ethanol as transport fuel - Yu Bai; Lin Luo; Ester van der Voet (The International Journal of Life Cycle Assessment, 2010)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Hydrolysis activities of the particle of agarose-Ce4+ complex for compounds containing phosphodiester or peptide bonds - Lina Yu; Dongfeng Wang; Lin Su; Yi Luo; Liping Sun; Changhu Xue (Journal of Ocean University of China, 2005)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)